Development of GPS and GSM Based Distress Scene Locating and Reporting System. - Kiiza Daniel (Kabale University, 2023)
Distresses such as road accidents, highway robbery and vehicle fire have terrified and claimed many lives and property on our road transport networks. The most challenge here is that police and immediate people to the victims get notified of the incidents when it is too late to offer immediate help. Even after being notified, it takes a lot of time to locate the scene. Some systems have and are being developed to attempt to solve this problem reporting the scene to police but the biggest limitation these systems have is that they only report location coordinates to the connected telephone numbers. This kind of approach is inefficient as the response time is too much, this could be the respondent taking long to read the message, there should be a way of ensuring the message sent is delivered, read and response done as soon as possible in the shortest period of time. This project is about the development of Distress scene locating and reporting system using GPS and GSM technology that not only sends the location coordinates of the distress scene but also distress messages and also calls the respondent to ensure the attention of the respondent is attracted to the distress messages as urgent as possible. The project has been developed, tested and proved to be efficient at reducing the response time. The methodologies used to meet the objectives of the project, the results and discussions are all described in detail in the proceeding chapters of this report.